Efforts to Improve the Long Jump Ability of the Squart Style through Rubber Paralon Jump Exercises for PJKR-SD FIK UNM STUDENTS - Ikadarny, Ikadarny; Syafruddin , Muhammad Akbar (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
This research is an experimental research conducted to find out whether rubber paralon jumping training can improve the squatting style long jump ability of PJKR-SD FIK UNM students. This research was conducted at the Faculty of Sports Science, Makassar State University in the odd semester of 2024. The sample in this research was 20 male students of the PJKR-SD FIK UNM Study Program, which was determined using a random sampling technique. Data analysis was carried out using the paired sample t test using the SPSS application. Based on the results of data analysis, the sig (2-tailed) value of the pre-test and post-test data for students' squatting style long jump ability was 0.000 or <0.05 with a difference in mean value of -18.050. So it can be concluded that rubber paralon jumping training has been proven to be able to improve the long jump squatting style of PJKR-SD FIK UNM students.